The role of self-interacting right-handed neutrinos in galactic structure - Argüelles, Carlos Raúl (2016)
It has been shown previously that the DM in galactic halos can be explained by a self-gravitating system of massive keV fermions ('inos') in thermodynamic equilibrium, and predicted the existence of a denser quantum core of inos towards the center of galaxies. In this article we show that the inclusion of self-interactions among the inos, modeled within a relativistic mean-field-theory approach, allows the quantum core to become massive and compact enough to explain the dynamics of the S-cluster stars closest to the Milky Way's galactic center. The application of this model to other galaxies such as large elliptical harboring massive central dark objects of ∼ 109 Mo is also investigated. We identify these interacting inos with sterile right-handed neutrinos pertaining to minimal extensions of the Standard Model, and calculate the corresponding total cross-section σ within an electroweak-like formalism to be compared with other observationally inferred cross-section estimates. The coincidence of an ino mass range of few tens of keV derived here only from the galactic structure, with the range obtained independently from other astrophysical and cosmological constraints, points towards an important role of the right-handed neutrinos in the cosmic structure.